Peripartum cardiomyopathy management: insights from a Latin American case report - Torres-Valencia, Javier (2024)
Peripartum cardiomyopathy (PPCM) is a potentially life-threatening condition that can occur during the late pregnancy or puerperium. A 31-year-old woman with a recent twin pregnancy presented with heart failure symptoms nine days postpartum. On admission, she had volume overload and hemodynamic compromise, which was rapidly reversed with inotropic levosimendan support. Echocardiography revealed a left ventricular ejection fraction (LVEF) of 20% with global hypokinesia. Once stabilized, she was discharged on heart failure medication, bromocriptine, and warfarin. Cardiac magnetic resonance imaging at five weeks demonstrated a preserved LVEF of 57% and no evidence of myocardial scarring or edema. During the 4-year follow-up, the patient remained stable with no new pregnancies. This case highlights the importance of considering PPCM in the differential diagnosis of heart failure in the peripartum period after excluding other etiologies. It also describes the successful use of bromocriptine in facilitating recovery of systolic function without long-term complications.